2013
DOI: 10.1371/journal.pone.0059312
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Eye Contact in the West and East: Autonomic Responses and Evaluative Ratings

Abstract: Eye contact has a fundamental role in human social interaction. The special appearance of the human eye (i.e., white sclera contrasted with a coloured iris) implies the importance of detecting another person's face through eye contact. Empirical studies have demonstrated that faces making eye contact are detected quickly and processed preferentially (i.e., the eye contact effect). Such sensitivity to eye contact seems to be innate and universal among humans; however, several studies suggest that cultural norms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 52 publications
8
102
1
3
Order By: Relevance
“…They also reported differential effects of stimuli gaze direction upon face gaze behaviour across cultures; British participants were less affected by the gaze shift than Japanese participants, who shifted their fixation to the corresponding gaze direction of the stimulus face. These results are generally consistent with McCarthy et al [16,17], who reported that Caucasian adults tended to hold eye contact with an interviewer for longer durations when answering cognitively demanding questions, while Eastern Asian (Japanese) adults broke eye contact relatively easily in the same situation (but see also 18). Conversely, changes in mouth movements did not affect face gaze in either population in Senju et al [15].…”
Section: Introductionsupporting
confidence: 90%
“…They also reported differential effects of stimuli gaze direction upon face gaze behaviour across cultures; British participants were less affected by the gaze shift than Japanese participants, who shifted their fixation to the corresponding gaze direction of the stimulus face. These results are generally consistent with McCarthy et al [16,17], who reported that Caucasian adults tended to hold eye contact with an interviewer for longer durations when answering cognitively demanding questions, while Eastern Asian (Japanese) adults broke eye contact relatively easily in the same situation (but see also 18). Conversely, changes in mouth movements did not affect face gaze in either population in Senju et al [15].…”
Section: Introductionsupporting
confidence: 90%
“…This heart rate deceleration, thought to enhance attentional engagement with the stimulus and cognitive processing of the stimulus information, is affected by stimulus significance (“signal value”), which might have been associated with the stimulus either through innate readiness or learning [Öhman et al, ]. It was shown that direct gaze of another “live” individual triggers a greater heart rate deceleration than averted gaze in typical adult populations [Akechi et al, ; Myllyneva & Hietanen, ]. This deceleration response was also measured in Louwerse et al's [] study, which presented static facial pictures with different gaze directions to high‐functioning adolescents with ASD and typically developing controls.…”
Section: Introductionmentioning
confidence: 92%
“…HR deceleration response is an index of attention orienting to external stimuli (Graham & Clifton, ), amplified by affectively and motivationally salient stimuli (Bradley, ; Lang & Bradley, ). Consistent with behavioral studies showing that direct gaze captures and holds visual attention (e.g., Böckler et al ., ; Conty et al ., , Senju & Hasegawa, ; von Grünau & Anston, ), previous studies have shown enhanced HR deceleration responses to direct versus averted gaze (Akechi et al ., ). However, also this response has been shown to be modulated by the participants' belief of whether the other person can see or cannot see him/her during eye contact (Myllyneva & Hietanen, ).…”
Section: Introductionmentioning
confidence: 97%
“…For example, direct gaze attracts visual attention (Böckler, van der Wel & Welsh, ; Conty, Tijus, Hugueville, Coelho & George, ; Doi, Ueda & Shikohara, ; Lyyra, Astikainen & Hietanen, ; Senju & Hasegawa, ; von Grünau & Anston, ; for a critical view of visual search studies, see Cooper, Law & Langton, ), and lengthens total viewing times of faces (Palanica & Itier, ; Wieser, Pauli, Alpers & Mühlberger, ). Physiological measurements have shown that, compared to averted gaze, direct gaze induces greater heart rate deceleration responses indicative of attention orienting (Akechi, Senju, Uibo, Kikuchi, Hasegawa & Hietanen, ; Myllyneva & Hietanen, ) and heightened autonomic sympathetic arousal reflecting preparation for action as measured by skin conductance responses (SCR) (Helminen, Kaasinen & Hietanen, ; Hietanen, Leppänen, Peltola, Linna‐Aho & Ruuhiala, ; Nichols & Champness, ).…”
Section: Introductionmentioning
confidence: 99%